A copper alloy material and a method for producing the same

CN122941925APending Publication Date: 2026-10-20NINGBO POWERWAY ALLOY MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611142082.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]现有替代材料因强度不足(如高导电纯铜)、抗应力松弛性不佳、高温性能差、或耐蚀性及加工性受限(如部分Fe-P系合金)等问题,难以全面满足高端电子、新能源汽车等应用场景对可靠性、寿命与成本的综合平衡要求

Benefits of technology

[0031]与现有技术相比,本发明具有如下优点:本发明通过添加Zn元素,协同调控Fe、Ti和Cr元素含量,使本发明铜合金材料具有优异的强度(抗拉强度≥550MPa)、导电率(≥38%IACS)、抗应力松弛性(150℃/1000h条件下的抗热应力保持率≥75%)、弯折性能(Badway90°弯折R/t≤2.5不开裂)及镀层高温附着力(130℃保持1000h无脱落)优异综合性能,从而满足高端电子、新能源汽车等应用场景对可靠性、寿命与成本的综合平衡要求,可广泛应用于汽车连接器等领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a copper alloy material with the following weight percentage composition: 3.0~10.0wt% Zn, 0.2~1.0wt% Cr, 0.01~0.6wt% Fe, 0.01~0.4wt% Ti, and 0~0.5wt% Z, with the balance being Cu and unavoidable impurities, wherein Z is selected from at least one element from Mg and Sn; in the weight percentage composition, the weight percentage content of Ti and Fe satisfies: Ti+Fe>0.15wt%. By adding Zn and optimizing the content of Cr, Fe, and Ti, this invention reduces costs while giving the copper alloy material excellent comprehensive properties such as strength, conductivity, stress relaxation resistance, bending performance, and high-temperature adhesion of the coating. This meets the comprehensive balance requirements of reliability, lifespan, and cost in high-end electronics, new energy vehicles, and other application scenarios, and can be widely used in fields such as automotive connectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of copper alloy technology, specifically relating to a copper alloy material and its preparation method. This copper alloy material is a low-cost copper-zinc-chromium-iron-titanium alloy material that can be applied to fields such as automotive connectors. Background Technology

[0002] With the rapid development of high-end electronics, new energy vehicles and other application fields, copper-nickel-silicon alloys such as C19010, C64750 and C70250 have become the preferred materials for core components such as lead frames, high-voltage connectors and battery terminals due to their high strength (tensile strength of over 550MPa), good conductivity (35~65%IACS) and excellent stress relaxation resistance and bending performance.

[0003] However, among current mainstream high-performance copper alloys, the high cost of copper-nickel-silicon alloys such as C70250 severely restricts their large-scale promotion in various application scenarios. On the other hand, in some general connector or low-to-medium voltage electrical connection scenarios where the mechanical performance requirements are slightly lower than the C70250 standard, continuing to use C70250 alloys results in significant performance overkill. Furthermore, its high nickel (2.2~4.2wt%) and silicon (0.25~1.2wt%) content not only drives up raw material costs but also imposes more stringent requirements on smelting and heat treatment processes. Meanwhile, the new energy vehicle and consumer electronics industries have an increasingly urgent need for cost reduction and efficiency improvement, urgently requiring a new copper alloy solution that significantly reduces material costs while maintaining key performance characteristics (such as tensile strength ≥550MPa, conductivity ≥35%IACS, excellent stress relaxation resistance and bending performance).

[0004] Existing alternative materials suffer from insufficient strength (such as high-conductivity pure copper), poor stress relaxation resistance, poor high-temperature performance, or limitations in corrosion resistance and processability (such as some Fe-P alloys), making it difficult to fully meet the comprehensive balance requirements of reliability, lifespan, and cost for applications such as high-end electronics and new energy vehicles. Therefore, developing a new generation of copper alloy materials with optimized composition, strong process adaptability, controllable cost, and comprehensive performance indicators precisely matched to the application needs of high-end electronics and new energy vehicles has outstanding technical necessity and broad market value. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a copper alloy material and its preparation method in view of the shortcomings of the prior art. By adding Zn element and optimizing the content of elements such as Cr, Fe, and Ti, the copper alloy material can be made to have excellent comprehensive properties such as strength, conductivity, stress relaxation resistance, bending performance and high temperature adhesion of coating while reducing cost. It can meet the comprehensive balance requirements of reliability, life and cost in high-end electronics, new energy vehicles and other application scenarios, and can be widely used in automotive connectors and other fields.

[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problem is as follows: a copper alloy material, wherein the weight percentage composition of the copper alloy material includes: 3.0~10.0wt% Zn, 0.2~1.0wt% Cr, 0.01~0.6wt% Fe, 0.01~0.4wt% Ti, 0~0.5wt% Z, and the balance is Cu and unavoidable impurities, wherein Z is selected from at least one element selected from Mg and Sn; in the weight percentage composition of the copper alloy material, the weight percentage content of Ti and Fe satisfies: Ti+Fe>0.15wt%.

[0007] In this invention, 3.0~10.0 wt% Zn is added to the copper alloy material. Zn serves as the main alloying element, and its function is as follows: Firstly, Zn, as a major alloying element, dissolves in the Cu matrix, causing lattice distortion and producing a significant solid solution strengthening effect, thus improving tensile strength. Simultaneously, the addition of Zn reduces stacking fault energy and suppresses dynamic recovery. This benefits the maintenance of a high dislocation density during cold working, where the dislocation density is sufficient to contribute significantly to work hardening strength without significantly reducing conductivity due to excessive distortion. Furthermore, the accumulated deformation energy results in an extremely high nucleation rate once recrystallization occurs, forming fine and uniform recrystallized grains. High-density annealing twins also hinder grain growth, promoting fine-grain strengthening. If the Zn content is below 3.0%, solid solution strengthening and work hardening capabilities are insufficient, recrystallization is prone to over-recrystallization, and strength is difficult to achieve. If the Zn content is above 10.0%, lattice distortion intensifies, recrystallization is excessively suppressed, residual stress concentration intensifies, and the KAM value easily exceeds 3°. Although strength may increase, conductivity drops sharply, and bending performance deteriorates.

[0008] Secondly, the Zn element in this invention can also promote the formation of dispersed precipitates. These fine precipitates (i.e., the second phase) can effectively pin dislocations and subgrain boundaries, contributing significantly to the dispersion strengthening effect. If the Zn content is too low, the precipitation driving force is insufficient, the proportion of fine second phases decreases, and the strengthening effect and thermal stress retention rate are both limited. If the Zn content is too high, although it may increase the number of precipitates, it easily promotes the formation of coarse and brittle second phases (such as Cu5Zn8), reducing the proportion of fine particles with a size ≤2μm. This not only weakens the dispersion strengthening effect but also deteriorates the plasticity and bending performance, increasing the risk of Badway bending cracks and coating peeling.

[0009] This invention adds 0.2~1.0 wt% Cr to the copper alloy material. Cr provides excellent aging precipitation characteristics for the alloy material. During heat treatment, Cr precipitates as a fine, dispersed second phase (such as Cr nano-precipitates), providing a fine second phase dispersed in the copper matrix, thereby improving tensile strength through precipitation strengthening. More importantly, the Cr precipitates are small in size and have good conductivity, with weak electron scattering, which is more conducive to maintaining higher conductivity compared to other high-resistivity precipitates (such as NiSi and FeP). In addition, the Cr precipitates pin dislocations and grain boundaries, inhibiting grain growth at high temperatures and softening of the microstructure during stress relaxation, significantly improving the heat stress retention rate and high-temperature adhesion of the coating. When the Cr content is low, the number of precipitates is insufficient, the precipitation strengthening contribution is significantly weakened, it is difficult to compensate for work hardening losses, resulting in insufficient strength; at the same time, the pinning effect on grain boundaries and dislocations is weakened, recrystallization is prone to occur, the stress relaxation resistance decreases, and the high-temperature adhesion of the coating is insufficient. When the Cr content is too high, Cr supersaturation easily forms coarse primary precipitates (such as Cr particles). This not only consumes too much Cr and precipitates out, reducing the age hardening ability, but also becomes a stress concentration source, damaging plasticity and bending performance. At the same time, the coarse phase has a strong ability to scatter electrons, which can easily reduce conductivity. In addition, high Cr increases the tendency of casting segregation, affecting the material uniformity, processing consistency and the improvement of overall performance.

[0010] This invention involves adding 0.01~0.6 wt% Fe to the copper alloy material. Fe synergistically forms highly thermally stable composite precipitates (such as Fe-Cr or Fe-Ti enriched phases) with elements such as Cr and Ti, further enhancing precipitation strengthening and improving the high-temperature adhesion of the coating. These fine composite precipitates remain stable after cold working, effectively pinning dislocations and subgrain boundaries, delaying recrystallization nucleation and growth, and helping to retain some non-recrystallized structures, thereby maintaining high strength and work hardening potential. Simultaneously, the appropriate addition of Fe can improve the alloy's heat resistance, enhance the bonding stability of the tin plating layer under long-term aging at 130℃, and prevent aging and peeling after tin plating. When the Fe content is too low, it cannot effectively participate in the formation of Fe-Cr or Fe-Ti composite precipitates, weakening the precipitation strengthening and recrystallization inhibition effects; the grain boundary pinning ability decreases, the microstructure stability deteriorates during high-temperature service, and the thermal stress retention rate also decreases. Excessive Fe can easily form coarse, hard, and brittle Fe-rich second phases (such as Fe-Cr compounds), which severely disrupt the continuity of the matrix, significantly reduce plasticity and bending properties, and cause cracking during bending. At the same time, these phases have extremely poor electrical conductivity, which greatly drags down the overall conductivity. They may also accumulate at the coating interface, becoming the starting point for coating peeling.

[0011] This invention involves adding 0.01~0.4 wt% Ti to the copper alloy material. Ti has a strong deoxidizing ability and can combine with unavoidable impurity elements (such as C, O, S, etc.) to form high-melting-point compounds, purifying grain boundaries, reducing the distribution of brittle phases along grain boundaries, and significantly improving the plasticity and bending properties of the alloy material. Simultaneously, Ti can form fine TiFe or TiCr precipitates with Fe and Cr, further refining the grains and enhancing precipitation strengthening. These nanoprecipitates are uniformly distributed during aging, improving strength and, due to their low volume fraction and uniform distribution, minimizing interference with electron transport, thus helping to maintain conductivity. Furthermore, Ti can increase the recrystallization temperature, inhibit microstructure degradation during high-temperature service, enhance stress relaxation resistance, and inhibit high-temperature coating peeling. When the Ti content is below 0.01 wt%, the number of precipitates (such as TiFe) is low, resulting in weak precipitation strengthening and recrystallization inhibition, affecting strength and thermal stability. When the Ti content exceeds 0.4 wt%, it reacts with elements such as Fe and Cr to form coarse intermetallic compounds such as TiFe and TiCr, or segregation occurs during solidification, leading to decreased plasticity, increased risk of bending cracks, and affecting conductivity and microstructure uniformity. Therefore, the Ti content should be controlled within the range of 0.01~0.4 wt% to achieve the optimal balance between precipitation strengthening and microstructure stability.

[0012] In the copper alloy material of this invention, the weight percentage content of Ti and Fe satisfies: Ti + Fe > 0.15 wt%, to promote the formation of a sufficient number of fine and dispersed TiFe precipitates, achieving a synergistic effect of precipitation strengthening and recrystallization inhibition. Compared with single-element precipitation, TiFe composite precipitation is easier to control in size and density, avoiding the formation of coarse phases. The fine and dispersed TiFe precipitates can effectively pin dislocations, subgrain boundaries, and grain boundaries, hindering recrystallization nucleation and grain growth. This helps to retain some non-recrystallized structures or fine-grained structures during annealing or high-temperature service, maintaining high strength levels and significantly improving thermal stress retention and high-temperature coating adhesion. Simultaneously, the presence of Fe can lower the diffusion barrier of Ti, promoting rapid nucleation of the TiFe phase at lower temperatures; while Ti can stabilize the precipitation behavior of Fe, preventing its aggregation into coarse Fe-rich phases. When the total Ti and Fe content is less than 0.15 wt%, the precipitate density is insufficient, leading to a decrease in strength and thermal stability.

[0013] The copper alloy material of this invention also contains 0-0.5 wt% Z, where Z is at least one element selected from Mg and Sn. Mg can participate in the deoxidation reaction during the smelting process, helping to reduce the oxygen content and purify the matrix. Simultaneously, as a substitutional solute atom, Mg can interact elastically with dislocations, hindering dislocation movement and enhancing the solid solution strengthening effect, thereby significantly improving the material's resistance to stress relaxation and high-temperature softening. Appropriate amounts of Mg may also improve the interfacial bonding between the coating and the substrate, reducing the tendency for delamination during thermal aging. Sn can significantly reduce the stacking fault energy of the copper matrix, inhibit dislocation cross-slip, and enhance work hardening ability. Under appropriate conditions, Sn, Zn, and other microalloying elements work synergistically to promote the formation of fine, dispersed precipitates, increasing the proportion of second phases with a particle size ≤2 μm, thereby optimizing the microstructure uniformity. The addition of Sn can also improve the material's corrosion resistance and coating wettability. When Mg and Sn are added together, the grain boundary pinning effect dominated by Mg and the dislocation structure evolution induced by Sn jointly affect the recrystallization kinetics. Under reasonable composition and process control, the microstructure refinement, strength improvement and conductivity can be optimized in a coordinated manner. By controlling the total Z content to within 0.5 wt%, the scattering effect of solid solution atoms on electrons can be effectively reduced, avoiding the increase in brittleness caused by grain boundary segregation, thereby maintaining good bending performance while ensuring high conductivity.

[0014] In the copper alloy material of the present invention, apart from the necessary components and optional additives, the balance is copper and unavoidable impurities; the unavoidable impurities refer to non-metallic elements such as S, O, C, H, and N, as well as metallic elements such as As, Pb, and Bi, which are inherent in the raw materials or unintentionally mixed in during the manufacturing process and whose content is extremely low and does not affect the alloy performance. The total content of these impurities is preferably controlled below 0.1 wt%.

[0015] Preferably, in the microstructure of the copper alloy material of the present invention, the area ratio of recrystallized structure in the cross-section (i.e., the cross-section perpendicular to the rolling direction) is 2-55%, realizing a dual-structure composite structure of "non-recrystallized structure + partially recrystallized structure". This microstructure combines the advantages of both structures, possessing the synergistic effect of dispersion strengthening and partial recovery structure. The non-recrystallized region provides high-strength work hardening contribution and fine precipitate distribution (dense precipitation along dislocations), while the recrystallized region provides a path for releasing deformation energy, improving plasticity and reducing residual stress concentration. Together, they enable the material to achieve a good balance between strength, conductivity, bending workability, stress relaxation resistance, and high-temperature adhesion of the coating. If the area ratio of recrystallized structure is less than 2%, the matrix relies on high-density dislocations and deformation energy storage for strengthening, resulting in high tensile strength and significant work hardening effect. However, the dense dislocations lead to stress concentration, poor bending performance, strong electron scattering, and low conductivity. During service, recovery and recrystallization are prone to occur, resulting in weak stress relaxation resistance. If the area ratio of recrystallized structure is higher than 55%, the formation of distortion-free equiaxed crystals by eliminating dislocations results in good plasticity and excellent bending performance, but the strength is significantly reduced, relying only on precipitation strengthening and grain refinement strengthening; the increase in grain boundaries slightly reduces conductivity, and the precipitated phase is prone to coarsening at high temperatures, resulting in insufficient high-temperature adhesion and stress relaxation resistance of the coating.

[0016] Preferably, in the microstructure of the copper alloy material cross-section of the present invention, the area ratio of deformed structure is 35-85%; the area ratio of the deformed structure is denoted as D, and the area ratio of the recrystallized structure is denoted as R, and the ratio of D to R satisfies: 0.5 ≤ D / R ≤ 20. This ratio reflects the quantitative balance between work-hardened structure and recrystallized softened structure: when D / R ≥ 0.5, sufficient deformed structure provides high dislocation density and work hardening contribution, combined with the dispersion strengthening effect of fine second phase, further ensuring that the tensile strength reaches above 550 MPa; at the same time, D / R ≤ 20 ensures that not less than 0.5% of recrystallized structure releases residual stress, refines grains, prevents cracking when Badway 90° bend R / t ≤ 2.5, ensures the stability of high-temperature coating, and avoids the decrease in conductivity caused by excessive work hardening. If D / R < 0.5, the recrystallization ratio is too high, the work hardening contribution is insufficient, and the strength is difficult to meet the standard; if D / R > 20, there is excessive deformation structure, residual stress concentration, deterioration of bending performance, and low thermal stress retention rate.

[0017] Preferably, the average KAM value in the cross-section of the copper alloy material of the present invention is below 3.0°. This allows for the simultaneous attainment of excellent strength, conductivity, bending workability, stress relaxation resistance, and high-temperature coating adhesion, specifically as follows: First, when the average KAM value is ≤3.0°, the dislocation density and microstrain within the copper alloy are within a moderate range. This range provides sufficient work hardening through grain refinement and dispersion strengthening to improve strength, while avoiding excessive electron scattering due to excessive microstrain, thus maintaining excellent conductivity. If the average KAM value exceeds 3.0°, the microstrain increases significantly, and the dislocation density becomes too high. This leads to a sharp decrease in conductivity and, conversely, excessive work hardening reduces the material's plasticity. Although tensile strength may increase, bending performance deteriorates.

[0018] Secondly, the KAM average value of this invention is ≤3.0°, resulting in uniform internal deformation structure and a smooth residual stress distribution in the copper alloy material. This leads to extremely low anisotropy during bending, effectively suppressing microstructural fluctuations at different locations within the material and ensuring the uniformity of its mechanical and electrical properties. This is beneficial for improving the yield of subsequent high-speed stamping and bending forming, meeting the requirements of high-precision terminals, connectors, and other products with complex bending shapes. Conversely, when the KAM average value exceeds 3.0°, a large local strain gradient exists within the material, significantly increasing anisotropy. Bending in the negative direction easily produces edge cracks or surface orange peel under R / t=2.5 conditions, and even in the positive direction, tight bending with R / t=0 cannot be achieved.

[0019] Third, by controlling the average KAM value below 3.0°, the dislocation density in the copper alloy material of this invention is appropriate and uniformly distributed, without excessive deformation energy storage. Under continuous external force or high temperature environment, this stable microstructure can effectively suppress dislocation slip, creep, and early recrystallization. The microstructure with a low and uniform initial KAM value allows for smooth strain energy release during stress relaxation, avoiding accelerated relaxation caused by local strain concentration. This enables the material to maintain high residual stress under long-term load conditions, significantly improving the contact reliability of elastic components such as terminals and connectors, as well as the stability of high-temperature coatings.

[0020] Preferably, in the microstructure of the copper alloy material cross-section of the present invention, the distribution density of the second phase is ≥2×10⁻⁶. 4 pcs / mm 2The second phase with a particle size ≤2μm accounts for more than 65% of the total number of second phases, while the second phase with a particle size ≥5μm accounts for less than 5% of the total number of second phases. Based on extensive experimental research, the inventors discovered that the distribution density of the second phase with a particle size ≥0.05μm and the proportion of different particle sizes have a decisive influence on the overall performance of the copper alloy of this invention. Therefore, this invention significantly improves the overall performance of the copper alloy material by precisely controlling the distribution density of the second phase and the proportion of second phases with particle sizes ≤2μm and ≥5μm within the range of particle size ≥0.05μm. With the same proportion of second phases, smaller particle sizes result in a stronger pinning effect on recrystallization, leading to a corresponding decrease in recrystallized grain size. With the same particle size, increasing the proportion of particles results in a smaller recrystallized grain size and a better overall performance enhancement effect. In this invention, over 65% of the second phase consists of fine precipitates with a size controlled below 2 μm, dispersed at subgrain boundaries and dislocation entanglements. When recrystallization nuclei attempt to migrate and grow into the deformed matrix, their high dispersion and density create a strong pinning effect on the recrystallization grain boundaries, hindering grain boundary movement. When the driving force for grain boundary migration exceeds the pinning resistance, recrystallization is further promoted, further enhancing the overall performance. Furthermore, by controlling the proportion and distribution of fine and coarse second phases, this invention further ensures that the area ratio of the recrystallized structure remains within the range of 2–55% and tends towards stability.

[0021] Preferably, the copper alloy material further includes 0.001~1.0 wt% of X, selected from one or more elements chosen from Zr, Co, P, Mn, Al, Si, Ni, Ag, and RE (rare earth elements), to further regulate precipitation behavior, purify grain boundaries, enhance strength, or improve processing performance. Adding trace amounts of P or Zr to the alloy of this invention can significantly refine the grains. P can form a high-melting-point Cu3P phase with Cu, acting as a heterogeneous nucleation core to promote solidification microstructure refinement; Zr, by forming high-melting-point intermetallic compounds (such as ZrCu5) or oxide inclusions, inhibits grain growth in the early stages of solidification, thereby obtaining a uniform and fine as-cast microstructure. Grain refinement not only improves the matching of room-temperature strength and plasticity of the alloy but also helps improve subsequent rolling and bending forming capabilities. The addition of Al (if coexisting with Ni) can form fine, dispersed NiAl-type intermetallic compounds with Ni, providing precipitation strengthening and enhancing alloy strength. On the other hand, Al preferentially oxidizes on the alloy surface to form a dense, stable Al₂O₃ passivation film, effectively blocking environmental corrosion and significantly improving the alloy's corrosion resistance in humid, weakly acidic, or chloride-ion environments, thus extending the alloy's service life. Rare earth elements (REs) selected from single or mixed rare earth elements have a significant grain boundary purification effect in the copper alloy material of this invention; mixed rare earth elements can also effectively improve the strength of the alloy material. Each trace element can exert a synergistic effect within a limited range, enhancing the overall performance of the alloy material. However, when the total content exceeds 1.0 wt%, it easily leads to the precipitation of coarse phases, decreased conductivity, or deterioration of plasticity; when it is below 0.001 wt%, the overall performance enhancement effect is limited.

[0022] The copper alloy material of this invention has a tensile strength ≥550MPa, conductivity ≥38%IACS, thermal stress retention rate ≥75% under 150℃ / 1000h conditions, no cracking under Badway 90° bending R / t≤2.5, and no peeling after hot-dip plating or electroplating at 130℃ for 1000h.

[0023] The copper alloy material of this invention can be made into plates, strips, bars, wires, etc., as needed.

[0024] This invention also provides a method for preparing the above-mentioned copper alloy material, comprising the following preparation process: casting → hot rolling → cold rolling → annealing, with specific steps as follows: (1) Melting and casting: In the melting and casting process of the preparation method of the present invention, the melting temperature is 1200~1350℃, the casting temperature is 1150~1280℃, and the casting speed is 40~100mm / min. Melting is divided into two stages: the first stage melting temperature is 1250~1350℃; the second stage melting temperature is 1200~1300℃. In the first stage of melting, high melting point furnace materials such as copper, iron, and copper-chromium alloys are put into the melting furnace and fully melted and homogenized at 1250~1350℃ to ensure that all alloy elements are completely dissolved in the copper matrix. If the temperature is insufficient or the holding time is insufficient, chromium will remain in the ingot as coarse chromium-rich particles, which not only consumes the effective chromium content and weakens the subsequent precipitation strengthening effect, but also makes it difficult for the proportion of fine second phase ≤2μm to reach more than 65%. At the same time, these coarse particles cannot be eliminated in the subsequent deformation and heat treatment process, and will become the source of bending cracks and the cause of coating peeling. The second stage of smelting involves cooling to 1200–1300℃ and adding zinc, copper-titanium master alloys, and other optional elements. Excessive temperature can lead to zinc vapor escaping and introducing porosity and oxide inclusions into the melt, affecting conductivity. Adding zinc at 1200–1300℃ effectively controls zinc burn-off, ensuring its full performance in solid solution strengthening and stacking fault energy regulation. Titanium, similarly, must be added in this temperature range as a copper-titanium master alloy to effectively control oxidation burn-off and ensure its uniform distribution in the matrix in a fine, dispersed form. Other optional elements added at this temperature (such as Mg and Sn) also avoid high-temperature volatilization and excessive oxidation, ensuring they effectively pin grain boundaries and refine grains. Adding them at higher temperatures would cause titanium to react with oxygen, easily forming inclusions and reducing the effective titanium content. Furthermore, large inclusions would become stress concentration points in subsequent microstructures, deteriorating bending performance and coating adhesion. The alloy of this invention is cast at 1150–1280℃ with a casting speed controlled at 40–100 mm / min. This results in a fine-grained, uniform, and segregated as-cast microstructure, avoiding the formation of coarse primary phases and porosity defects. This ensures uniform dislocation density accumulation during subsequent cold working deformation, which is beneficial for stable control of the KAM value. At the same time, the uniform as-cast microstructure provides precursor conditions for the recrystallization area ratio and the size distribution and density of the second phase particles. The fine as-cast grains and dispersed initial precipitates are more easily transformed into a uniform recrystallized microstructure during subsequent heat treatment, promoting the precipitation of fine and dispersed second phases. This has a positive contribution to the overall matching of strength, conductivity, bending performance, and thermal stress retention rate.

[0025] (2) Hot rolling: In the preparation method of this invention, the initial temperature of hot rolling is 800-1050℃, the holding time is 4-6h, 6-12 passes are used, the deformation per pass is not less than 10%, the rolling speed is 100-200mm / min, and rapid cooling is performed after final rolling. The deformation per pass is not less than 10% to ensure that the deformation of each pass can penetrate the entire cross section, effectively break up the cast coarse dendrites and promote the full nucleation of dynamic recrystallization; if it is less than 10%, the deformation is limited to the surface layer, and the core still retains the cast coarse grains and segregation, resulting in uneven cross section structure, discrete KAM value distribution and difficulty in uniform recrystallization, and the D / R ratio is prone to deviate from the range of 0.5-20; if the deformation per pass is too large, the single energy storage is too high and it is easy to cause local abnormal recrystallization or temperature rise leading to abnormal grain growth. The rolling speed should be matched with 6-12 passes and the deformation amount per pass (not less than 10%) to avoid insufficient reduction due to too few passes or excessive strain accumulation due to too many passes. This prevents the recrystallization area from exceeding the range of 2-55%, which would otherwise lead to poor bending performance, low conductivity, easy recovery and recrystallization during service, weak resistance to stress relaxation, and insufficient adhesion of high-temperature coatings. Rolling speed control prevents localized overheating or grain coarsening, and rapid cooling fixes the deformed structure and dynamic recrystallization ratio while retaining dispersed precipitates.

[0026] (3) Cold rolling: In the preparation method of this invention, the cumulative deformation of cold rolling is more than 50%. On the one hand, the material is gradually thinned to the target size through multiple rolling passes; on the other hand, the dislocation slip and grain refinement mechanisms are fully activated to improve the strength and hardness of the material, while forming a uniform processing texture, which provides a favorable microstructure for subsequent heat treatment. Since cold rolling is carried out below the recrystallization temperature, the material will be accompanied by work hardening. Therefore, it is necessary to reasonably allocate the reduction amount and total deformation amount of each pass, control the rolling force and the stability of the alloy material, and avoid defects such as fracture or surface scratches. By controlling the deformation amount to be more than 50%, a cold-rolled copper alloy material with high dimensional accuracy, smooth surface, dense microstructure and good comprehensive performance is finally obtained. In addition, the hot-rolled billet is first surface-treated before cold rolling to thoroughly remove the surface oxide layer and attached impurities to ensure the surface quality of subsequent processing and prevent defects from being pressed into the matrix during cold rolling, causing stress concentration or surface cracks.

[0027] (4) Annealing: In the preparation method of this invention, annealing is carried out at a low temperature of 300-500℃ for 4-12 hours. At this temperature, the alloy material undergoes a sufficient recovery process first. The high-density dislocations introduced by cold rolling are rearranged through slip and climb, causing the KAM value to gradually decrease from the high position of the cold-rolled state to below 3°. This promotes the release of micro-strain and the optimization of dislocation density, which not only retains sufficient dislocation density to strengthen the strength, but also avoids the damage to bending performance and conductivity caused by excessive strain concentration. In addition, the recrystallization area ratio is precisely controlled between 2% and 55%. That is, a recrystallization ratio closer to the lower limit is obtained by a shorter holding time (4-6h) to enhance work hardening, or a recrystallization ratio closer to the upper limit is obtained by a longer holding time (8-12h) to further improve plasticity and bending performance. On the one hand, alloying elements such as Fe, Cr, and Ti dissolved in the matrix are fully precipitated as fine, dispersed second phases, and the precipitated phases are confined to the submicron scale, increasing the proportion of fine second phases and effectively pinning dislocations and subgrain boundaries, contributing significantly to dispersion strengthening. On the other hand, the migration of recrystallized grain boundaries and grain growth are effectively suppressed by the pinning effect of the precipitated phases, avoiding grain coarsening and maintaining the fineness and uniformity of the microstructure. If the annealing temperature is below 300℃ or the time is less than 4h, the recovery is insufficient, the KAM value is still higher than 3°, the dislocation density is too high, leading to increased electron scattering, and the conductivity is difficult to achieve the target. At the same time, the residual stress concentration makes the bending in the bad direction worse. If the annealing temperature is above 500℃ or the time is longer than 12h, recrystallization is excessive, the contribution of work hardening is weakened, the tensile strength may be insufficient, and the proportion of fine second phases decreases, the dispersion strengthening effect decreases, and the heat stress retention rate also decreases.

[0028] Preferably, in the preparation method of the present invention, after the annealing in step (4) above, the alloy material is subjected to a second cold rolling in step (5) and a second annealing in step (6) to further improve the strength and electrical conductivity of the alloy material. Among them, the annealing in step (4) can also be carried out by high-temperature rapid annealing at 501~1000℃ for 1~300 seconds, instead of the low-temperature long time in step (4) above. By rapidly heating the alloy material to a high temperature through high-temperature rapid annealing, recrystallization is completed quickly, and short-term heat preservation can effectively avoid grain growth and coarsening of precipitates, maintaining fine density of the microstructure while restoring plasticity; this process has a very short time, high production efficiency, low energy consumption, and is suitable for the fast pace of continuous production lines, and the solute elements diffuse fully at high temperature, which is conducive to obtaining a uniform microstructure. The two processes can be flexibly selected according to production efficiency and performance targets. The deformation amount of the second cold rolling in step (5) is not less than 20% to introduce an appropriate amount of dislocation density and control the texture evolution; the second annealing in step (6) is held at 300-500℃ for 4-12 hours to ensure that recrystallization is fully carried out while inhibiting grain coarsening, which is conducive to stabilizing the KAM value within 3° and promoting the precipitation of fine second phase with a high proportion, further optimizing the comprehensive performance of strength, conductivity, bending performance and high temperature coating adhesion.

[0029] Preferably, a solution treatment process is added between the hot rolling in step (2) and the cold rolling in step (3) to improve the tensile strength and bending formability of the alloy material. The solution temperature is 700-1100℃ and the time is 1-600 seconds to allow the alloying elements to fully dissolve in the matrix and form a uniform solid solution, providing conditions for subsequent precipitation strengthening. After the heat treatment, a rapid cooling method (water, water mist or other cooling medium) is used to suppress the precipitation of harmful phases. In terms of strength, the full solution treatment allows alloying elements such as Fe, Cr, and Ti to completely dissolve in the matrix, providing sufficient supersaturated solid solubility for the subsequent annealing stage and ensuring the precipitation strengthening effect. In terms of bending performance, the solution treatment eliminates the component segregation and coarse primary phases left over from the casting and hot working processes, resulting in a highly homogenized microstructure, significantly improving the plasticity and toughness of the material, and reducing stress concentration and cracking tendency during bending. Placing solution treatment before cold rolling allows for the accumulation of uniform and high-density dislocations in the homogeneous solid solution during subsequent large-deformation cold rolling. These uniformly distributed dislocations provide ample and uniformly distributed nucleation sites for the precipitates in the subsequent annealing stage. Simultaneously, rapid cooling after solution treatment retains a large number of supersaturated vacancies. These vacancies promote the diffusion of solute atoms and the uniform nucleation of the precipitates during subsequent aging, further refining the precipitates and ensuring a high proportion of fine second phases.

[0030] In addition to the main processes mentioned above, auxiliary processes such as milling and pickling can be added before or after the main processes as needed.

[0031] Compared with the prior art, the present invention has the following advantages: By adding Zn element and synergistically controlling the content of Fe, Ti and Cr elements, the copper alloy material of the present invention has excellent comprehensive performance in terms of strength (tensile strength ≥550MPa), conductivity (≥38%IACS), stress relaxation resistance (heat stress retention rate ≥75% under 150℃ / 1000h conditions), bending performance (no cracking after a Badway 90° bend R / t≤2.5), and high-temperature adhesion of the coating (no peeling after 1000h at 130℃). Thus, it meets the comprehensive balance requirements of reliability, lifespan and cost in high-end electronics, new energy vehicles and other application scenarios, and can be widely used in automotive connectors and other fields. Attached Figure Description

[0032] Figure 1 The image shows the microstructure of the copper alloy sample from Example 5, which is a statistical analysis of the recrystallization ratio on the cross-section. Figure 2 The image shows a microstructure of the copper alloy sample of Example 5, showing the distribution of the second phase of different sizes on a cross-section. Detailed Implementation

[0033] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0034] This invention selected 20 alloys from the embodiments and 2 alloys from the comparative examples. The chemical composition of the alloys is shown in Table 1. The main process flow for preparing the alloy materials of each embodiment and the comparative examples is: casting → hot rolling → cold rolling → annealing, specifically including the following steps: (1) Melting and casting: According to the composition in Table 1, high-melting-point furnace materials such as copper, iron, and copper-chromium alloy are first put into the melting furnace and fully melted at 1250-1350℃. Then, the temperature is lowered to 1200-1300℃, and zinc, copper-titanium master alloy and other optional elements are added. Then, ingots are cast at a temperature of 1150-1280℃ and a casting speed of 40-100 mm / min.

[0035] (2) Hot rolling: The ingot obtained in step (1) is hot rolled at a temperature of 800-1050℃ and a holding time of 4-6h. It is rolled in 6-12 passes with a single pass deformation of not less than 10% and a rolling speed of 100-200mm / min. After final rolling, it is cooled quickly and then the hot-rolled product is milled to remove surface impurities.

[0036] (3) Cold rolling: The hot-rolled product obtained in step (2) is cold-rolled with a processing rate of not less than 50%.

[0037] (4) Annealing: The sample obtained in step (3) is annealed at a temperature of 300-500℃ for 4-12 hours. After annealing, it is cleaned to obtain the sample of the required specifications.

[0038] The detailed parameters of the key process steps are shown in Table 2.

[0039] The properties of the various embodiments and comparative alloy samples obtained in this invention were evaluated under the following conditions.

[0040] Tensile strength test: The test was conducted on an electronic universal mechanical property testing machine in accordance with GB / T 228.1-2021 Metallic materials, tensile testing - Part 1: Test method at room temperature, with a tensile speed of 5 mm / min.

[0041] Conductivity test: The conductivity of the materials in the examples and comparative examples was tested according to GB / T 32791-2016 "Eddy Current Test Method for Conductivity of Copper and Copper Alloys".

[0042] Bending test: The Badway 90° bending test performance of the sample and comparative materials was tested according to the "YS / T 1773-2025 Test Method for Bending of Copper and Copper Alloy Strips and Foils".

[0043] Thermal stress retention rate test: The thermal stress retention rate of the sample and comparative materials was tested according to GB / T 39152-2020 Test Method for Bending Stress Relaxation of Copper and Copper Alloys. The test conditions were: the exposure temperature was 150℃ and the test time was 1000h.

[0044] Hot-dip plating or electroplating test: First, the sample is tin-plated to a thickness of 1.5 μm. Then, the tin-plated sample is bent at 90° and finally baked at 130°C for 1000 hours. The surface plating peeling is observed. No peeling is indicated as "OK", slight peeling is indicated as "OK / NO", and severe peeling is indicated as "NO".

[0045] The area ratios of deformed and recrystallized structures were tested according to the basic principles of grain identification and statistics in GB / T36165-2018, "Determination of Average Grain Size of Metals - Electron Backscatter Diffraction (EBSD) Method". Measurements were performed on an electron backscatter diffraction (EBSD) system equipped with a scanning electron microscope (SEM). The scanning area was set to 50 μm × 50 μm, and the scanning step size was 1 μm. Orientation data was acquired using EBSD, and recrystallized grains were identified using the accompanying software, combining grain orientation difference, grain boundary characteristics, and grain morphology parameters. The area ratios of deformed and recrystallized structures were automatically calculated. At least five regions of the cross-section of each copper alloy material were tested, and the average value was taken as the final area ratio result.

[0046] KAM average value test: Performed on an EBSD system of a scanning electron microscope (SEM). The scanning area was set to 50 μm × 50 μm, the scanning step size was 1 μm, and the system acquired crystal orientation data point by point according to the grid. Then, the EBSD software automatically calculated the KAM value according to the formula, and the KAM average value was calculated for more than 5 regions.

[0047] Second phase testing: Referring to "YS / T 449-2002 Methods for Microstructural Inspection of Copper and Copper Alloy Castings and Processed Products", electrolytic or chemical etching methods were used to clearly visualize the precipitated phases, and scanning electron microscopy (SEM) was selected for imaging. During imaging, five or more fields of view were randomly selected. Image analysis software such as ImageJ was used to separate the precipitated phases from the matrix by adjusting the threshold through binarization. The number of second phase particles with a diameter ≥0.05μm (i.e., circumscribed circle diameter ≥0.05μm) in each field of view was counted, and the distribution density of the second phase in a single field of view (unit: particles / mm) was calculated. 2 The calculation formula is: The distribution density of the second phase = the number of second phases / the field area.

[0048] Finally, the arithmetic mean of the distribution density of the second phase in each field of view is taken as the statistical value of the distribution density of the second phase in this invention.

[0049] The total number of second phase particles with a diameter ≥ 0.05 µm in each field of view is denoted as A; the number of second phase particles with a diameter in the range of 0.05–2.0 µm is denoted as B; and the number of second phase particles with a diameter ≥ 5 µm is denoted as C. Based on this, the following calculations are performed: 1) The proportion of the second phase with a particle size ≤ 2.0 μm is B / A; 2) The proportion of the second phase with a particle size ≥ 5.0 μm is C / A.

[0050] After calculating the proportion of the second phase at different sizes for each field of view, the average proportion of the second phase at different sizes for each field of view is finally calculated as the statistical value of this invention.

[0051] The properties of the alloys in the examples and comparative examples are shown in Table 3.

[0052] Micrographs showing the statistical recrystallization ratio on the cross-section of the copper alloy sample in Example 5 are shown below. Figure 1 Micrographs of the second phase distribution at different sizes are shown below. Figure 2 .Depend on Figure 1 and Figure 2 As can be seen, in Example 5, the recrystallized structure accounts for 33% of the area, the deformed structure accounts for 61%, and the subcrystalline structure accounts for 6%; the distribution density of the second phase is 4.5 × 10⁻⁶. 4 pcs / mm 2The second phase with a particle size ≤2μm accounts for 90% of the total number of second phases, while the second phase with a particle size ≥5μm accounts for 3.2%. This copper alloy material achieves a tensile strength of 610MPa, a conductivity of 49% IACS, a thermal stress retention rate of 82% under 150℃ / 1000h conditions, no cracking under a Badway 90° bend R / t ≤2.5, and no peeling after hot-dip plating or electroplating at 130℃ for 1000h. It meets the comprehensive balance requirements of reliability, lifespan, and cost for applications such as high-end electronics and new energy vehicles.

[0053] Table 1: Chemical composition of alloys in the examples and comparative examples

[0054] Table 2: Detailed parameters of key process steps for each embodiment and comparative alloy

[0055] Table 3: Properties of Alloys from Examples and Comparative Examples

[0056] Table 4. Microstructure of Examples and Comparative Examples

Claims

1. A copper alloy material, characterized in that, The weight percentage composition of the copper alloy material includes: 3.0~10.0wt% Zn, 0.2~1.0wt% Cr, 0.01~0.6wt% Fe, 0.01~0.4wt% Ti, 0~0.5wt% Z, with the balance being Cu and unavoidable impurities, wherein Z is selected from at least one element selected from Mg and Sn; in the weight percentage composition of the copper alloy material, the weight percentage content of Ti and Fe satisfies: Ti+Fe>0.15wt%.

2. The copper alloy material according to claim 1, characterized in that, In the microstructure of the cross-section of the copper alloy material, the area of ​​recrystallized structure accounts for 2-55%.

3. The copper alloy material according to claim 2, characterized in that, In the microstructure of the cross-section of the copper alloy material, the area ratio of the deformed structure is 35-85%; the area ratio of the deformed structure is denoted as D, and the area ratio of the recrystallized structure is denoted as R, and the ratio of D to R satisfies: 0.5≤D / R≤20.

4. The copper alloy material according to claim 1, characterized in that, In the microstructure of the cross-section of the copper alloy material, the average value of KAM is below 3.0°.

5. The copper alloy material according to claim 1, characterized in that, In the microstructure of the cross-section of the copper alloy material, the distribution density of the second phase is ≥2×10⁻⁶. 4 pcs / mm 2 The number of second phases with a particle size ≤2μm accounts for more than 65% of the total number of second phases, while the number of second phases with a particle size ≥5μm accounts for less than 5% of the total number of second phases.

6. The copper alloy material according to claim 1, characterized in that, The copper alloy material also includes 0.001 to 1.0 wt% of X, which is selected from one or more elements from Zr, Co, P, Mn, Al, Si, Ni, Ag, and RE.

7. The copper alloy material according to any one of claims 1 to 6, characterized in that, The copper alloy material has a tensile strength ≥550MPa, conductivity ≥38%IACS, thermal stress retention rate ≥75% under 150℃ / 1000h conditions, no cracking under Badway 90° bending R / t≤2.5, and no peeling after hot-dip plating or electroplating at 130℃ for 1000h.

8. A method for preparing the copper alloy material according to any one of claims 1 to 6, characterized in that, The preparation process of the copper alloy material is as follows: casting → hot rolling → cold rolling → annealing. The casting process is divided into two stages: the first stage melting temperature is 1250~1350℃, and the second stage melting temperature is 1200~1300℃.

9. The method for preparing the copper alloy material according to claim 8, characterized in that, The initial temperature of the hot rolling is 800~1050℃, the holding time is 4~6h, the number of rolling passes is 6~12, and the deformation per pass is not less than 10%.

10. The method for preparing the copper alloy material according to claim 8 or 9, characterized in that, The annealing temperature is 300~500℃, and the annealing time is 4~12 hours.